Weaving Abstraction - Wendy Red Star; Introduced by Josh T Franco (Archives of American Art Journal, 2023)
Wendy Red Star was the subject of two oral histories conducted by the Archives’ head of collecting Josh T. Franco, in 2020 and 2021, and so it is fitting that a conversation between them introduces her artwork for the journal. Committed to studying historical archives and oral traditions, Red Star literally weaves together passages from Joan Mitchell’s paintings with pages from the transcript of Mitchell’s 1986 oral history for the Archives, conducted by feminist art historian Linda Nochlin.